(untitled) (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: The main objective of the present research work was to develop floating microspheres of cefditoren pivoxel (CP) to provide the delivery of the drug at a sustained rate. Materials and Methods: Floating microspheres of CP were prepared by solvent evaporation technique using hydroxypropyl methylcellulose (HPMC) K4M and ethyl cellulose as the rate controlling polymers. The optimization of formulation was carried out by 32 factorial design using two factors; a total amount of polymer (X1) and concentration of ethyl cellulose (X2) as independent variables. The formulated floating microspheres were characterized by evaluating its yield, particle size, encapsulation efficiency, in vitro drug release, buoyancy, surface morphology (scanning electron microscopy analysis). Results and Discussion: The optimized formulation (F6) showed 91.5 Â± 1.35% of drug release after 12 h and 75 Â± 0.92% of entrapment efficiency. All the formulations have good buoyancy which was floated over 12 h in the dissolution medium. Conclusion: It can be concluded from the study that floating microspheres of CP can be prepared successfully using HPMC K4M and ethyl cellulose as the rate controlling polymers.